PENINGKATAN MENTAL HEALTH DAN WELL-BEING BAGI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FIB-UB PADA MASA PANDEMI COVID-19 - Degeng, Dian (Faculty of Cultural Studies, Universitas Brawijaya, 2022)
Mental health has become a critical issue recently for young adults (students) around the world, and it is fitting that educational institutions, including in Indonesia, provide a key developmental context to equip students with lifelong mental health and wellbeing skills. The demands on students can replace their ability to cope, coupled, in many cases, with preexisting or newly manifested psychiatric symptoms. The findings of many surveys have highlighted the true severity of the student mental health crisis and are an urgent call to action for universities and government agencies because otherwise it risks an entire generation of students and the future of a nation. Regarding stigma in society, even in educational institutions themselves, the level of hiding the real problem poses a risk that tends to be higher than when we face and deal with this problem openly. Therefore, mental health support for students must be a top priority for our university leaders.